Diskursanalyse und radikale Interpretation. Davidsonianische Überlegungen zu Grenzen und Transformationen historischer Diskurse - Graf, Rüdiger (Österreichische Zeitschrift für Geschichtswissenschaften, 2005)
This paper argues for the reintroduction of historical actors into the analysis of historical discourses. In reviewing current theories, the piece focuses on the problems of (post-)Foucauldian discourse analysis in explaining discursive changes and determining the boundaries of discourses. Since it is not possible to overcome these difficulties within a (post-)structuralist theory of meaning, the author proposes a different approach. Using Donald Davidson’s philosophy of language and his theory of ›radical interpretation‹, the paper argues for an understanding of discourses as being constituted by a set of beliefs shared by the participants. This approach then allows empirical research to define the boundaries of discourses and to explain the transformations they undergo without endowing individual voices with too much linguistic freedom. In contrast to more static theories of discourse formation, the author conceptualizes all discourses as ›inter-discourses‹, and emphasises their heterogeneity and fluid character.